Literature Review: Improving Elementary School Students' Problem-Solving Skills Through the Discovery Learning Model Assisted by Canva Media - Ulfa, Mahdalena; Mirna Rosita; Mai Efi Diningrat; Novianti (Journal Informatic, Education and Management (JIEM), 2025)
This study aims to show how elementary school students can improve their problem-solving skills through the use of the Discovery Learning approach assisted by the use of Canva media. The method used is a literature study by analyzing a number of relevant scientific journals. The research findings show that the Discovery Learning model is able to increase students' active participation in learning and develop critical, creative, and problem-solving thinking skills. The use of Canva media as a visual medium supports every stage in discovery learning, such as the stimulation, data collection, and verification stages, so that the learning process becomes more interesting, interactive, and meaningful. In addition, the integration of Canva helps teachers in designing teaching materials that suit students' learning styles. Therefore, the application of the Discovery Learning model moderated by Canva media is an effective learning strategy to improve elementary school students' problem-solving skills.